Estudantes estrangeiros no Brasil: reflexões sobre questões interculturais e suas análises em sala de aula de PLE - Monique Nascimento Longordo (2014)
This study aims to identify and analyze cultural interpretations expressed in conversational interactions among exchange students, both at the beginning and at the end of their experience in Brazil. Based on these students reflections, an analysis of their understanding of Brazilian cultural codes and cultural differences is presented. Following, manners in which teachers of Portuguese as a foreign language (PFL) would approach in the classroom some of the foreign culture constructs, while integrating an intercultural perspective, are identified. The database used for this study consists of: a) two transcripts and filmed interactions among students, both at the beginning and at the end of their exchange experience; b) Audio-recordings of PFL teachers; and c) answers to questionnaires distributed to fifty students. Interactions were analyzed at a pragmatic and semantic level. This analysis was theoretically based on the micro and macro levels inherent to intercultural communication.